Coconut Lethal Yellowing Diseases: A Phytoplasma Threat to Palms of Global Economic and Social Significance - Gurr, Geoff M.; Johnson, Anne C.; Ash, Gavin J.; Wilson, Bree A. L.; Ero, Mark M.; Pilotti, Carmel A.; Dewhurst, Charles F.; You, Minsheng S. (Frontiers in Plant Science, 2016)
The recent discovery of Bogia Coconut Syndrome in Papua New Guinea is the first report of a lethal yellowing disease (LYD) in Oceania. Numerous outbreaks of LYDs of coconut have been recorded in the Caribbean and Africa since the late 19th century and have caused the death of millions of palms across several continents during the 20th century. Despite the severity of economic losses, it was only in the 1970s that the causes of LYDs were identified as phytoplasmas, a group of insect-transmitted bacteria associated with diseases in many other economically important crop species. Since the development of polymerase chain reaction (PCR) technology, knowledge of LYDs epidemiology, ecology and vectors has grown rapidly. There is no economically viable treatment for LYDs and vector-based management is hampered by the fact that vectors have been positively identified in very few cases despite many attempted transmission trials. Some varieties and hybrids of coconut palm are known to be less susceptible to LYD but none are completely resistant. Optimal and current management of LYD is through strict quarantine, prompt detection and destruction of symptomatic palms, and replanting with less susceptible varieties or crop species. Advances in technology such as loop mediated isothermal amplification (LAMP) for detection and tracking of phytoplasma DNA in plants and insects, remote sensing for identifying symptomatic palms, and the advent of clustered regularly interspaced short palindromic repeats (CRISPR)-based tools for gene editing and plant breeding are likely to allow rapid progress in taxonomy as well as understanding and managing LYD phytoplasma pathosystems.